Insights from the Household Roster on Demographics and Educational Attainment in Cox's Bazar - World Bank (World Bank, Washington, DC, 2021)
Administered to 5020 households, evenly split between Rohingya campsites and host communities, the household roster collects basic information on all members of the household. In addition to basic demographic characteristics, the module includes information on education for all members of the household. The descriptives confirm that the Bangladeshi population living in Cox’s Bazar is vulnerable and poor by national standards; and this was the case even before the influx of the Rohingya into the sub-districts of Teknaf and Ukhia. At the same time, the Rohingya population living in campsites faces high levels of need, and fare worse than the host community across a range of indicators related to household demographics and education.